Aplicação da soft-starter para acionamento de motores de indução acoplados a diferentes tipos de cargas mecânicas - Amaral, Rodrigo Sarmento do (2013)
This monograph has as its main theme the starting of induction motors using a soft-starter. Different mechanical load torques were applied and their starting responses were analyzed from a computational program simulation. For analyzing the motor starting, simplified simulations were performed by SDW CD 1.4 Weg software, aiming to obtain the machine characteristics and the loads behavior during the starting machine period. The results of the simulations showed the importance of a suitable design of the soft-starter to start a certain motor. These simulations didn‟t consider the influence of electromagnetic interferences due to the firing of the semiconductor devices (thyristors) of the soft-starter in the simulations results. The state of art and the state of practice of the soft-starter were also addressed.